THE ROLE OF NON-GOVERNMENTAL ORGANIZATIONS OF HORTING IN THE FORMATION OF HIGH SCHOOL STUDENT’S SOCIALLY SUCCESSFUL PERSONALITY - Necherda, Valeria (Theoretical and Methodical Problems of Children and Youth Education, 2021)
The article is devoted to one of the topical problems of modern psychological and pedagogical theory and educational practice – formation of high school student’ socially successful personality in general secondary education institution. The tasks of the proposed work are to generalize data on the phenomenon of social success and activities of non-governmental organizations in education of the younger generation, as well as analysis of the results of the application of appropriate methods aimed at clarifying the role of non-governmental organizations of horting in the formation of high school student’ socially successful personality. In the process of research were used theoretical methods (analysis, comparison and generalization), empirical methods (interviewing, blitz survey, method of unfinished sentences).The author considers the phenomenon of social success and socio-psychological features of high school students and clarifies the essence of the concepts of «social success» and «high school students’ socially successful personality». The paper emphasizes the need for partnership relations of general secondary education institutions with non-governmental organizations, defines the role of non-governmental organizations in education of the younger generation. It is established that more than half of high school students of experimental institutions from time to time participate in the activities of a certain non-governmental organization, and outlines the defining characteristics of horting as a general system of self-improvement of the individual and found that the participation of students in non-governmental organizations of horting is greater than other non-governmental organizations of military-patriotic and physical culture and sports.The proposed study identifies the necessary qualities for the social success of the student’s personality, the development of which involves horting education, and highlights the features of the use of «success situations» in horting. Based on the results obtained, the researcher comes to conclusions about the important role of non-governmental organizations of horting in the formation of high school students’ socially successful personality.